THE QUESTION OF ALIENATION IN HEGEL’S PHILOSOPHY (BETWEEN THE MANIFESTATION OF THE CONCEPT AND THE MULTIPLICITY OF MEANINGS) - Lasgaa Rabia, (International Journal of Innovative Technologies in Social Science, 2024)
As is well known, Hegel is one of the most famous philosophers who dealt with the problem of alienation in a profound philosophical manner. Therefore, he is considered by many scholars to be the “godfather of alienation,” through the ideas and theories he immortalized in important works, the most famous of which are the book “Phenomenology of Thought” (1807) and the book “Philosophy of Right,” in which he addressed the phenomenon of alienation based on concepts that confirm his intellectual originalityIn the first book, he addressed it within the framework of his analysis of the movement of consciousness, specifically the movement of philosophical consciousness, in which consciousness moves from abstract truth to sensory certainty and from there to the certainty of absolute knowledge. In The Philosophy of Right, however, alienation appears within the framework of Hegel's social philosophy. The fundamental problem we address here relates to Hegel's approach to the subject of alienation. How did he address it, and what meanings and connotations did he attribute to?